Definition of terms related to Buddhism found in ancient Turkic texts in the Sog script (According to the text of Sekiz yukmek yaruk) (Journal of Oriental Studies, 2023)
The article gives a definition of the terms related to Buddhism, found in ancient Turkic texts written in Sogdian script. These works, written in the ancient Uyghur language, are mainly religious translated texts, so they contain many religious terms, prayers and poems in the language of the country where the religion originated. It is necessary to know the origin of these terms in order to study the invaluable heritage left by our ancestors and introduce it into scientific activity in our native language. The purpose of the article is to explain the meaning of religious terms (including those related to Buddhism), which are often found in translated literary relics of ancient Uyghur writing, and to provide a reference book. In our article, we used religious terms from the “Sekiz Yukmek Yaruk” Sutra, which preaches Buddhism, which is widely known in the world of science. The relevance of the article lies in the fact that this topic in the Kazakh language has never been raised in Kazakh science, has not been studied scientifically. When writing the work "Eski Uygur Türkçesinde Budizm Ve Manihaizm Terimleri" ("Terms of Buddhism and Manichaeism in the Old Uyghur Turkic Language") by Hazher Tokyurek, "An Etimolojical Dictionary of Pre-Thirteenth-Century Turkish" by S. Clauson, "Eski Uygurca Altı Dişli Fil Hikayesi" (The Old Uighur Six-Toothed Elephant Story) by Murat Elmaly and M. Olmez. ‘Köktürkçe ve Eski Uygurca Dersleri’ (Old Turkic and Old Uyghur lectures) were used. The article uses comparative-historical, grouping, analytical and translation methods. This article is of great practical and theoretical importance, as it can be used as an auxiliary teaching aid in the subjects "History of Kazakh Literature", "History of Turkic Literature", "Introduction to Turkic Studies", "History of World Literature". Key words: ancient Uyghur language, Sogdian writing, Buddhism, religious terms, ancient Turkic literature.